The Roles of Acidosis in Osteoclast Biology - Yuan, Feng-Lai; Xu, Ming-Hui; Li, Xia; Xinlong, He; Fang, Wei; Dong, Jian (Frontiers in Physiology, 2016)
The adverse effect of acidosis on the skeletal system has been recognized for almost a century. Although the underlying mechanism has not been fully elucidated, it appears that acidosis acts as a general stimulator of osteoclasts derived from bone marrow precursors cells and enhances osteoclastic resorption. Prior work suggests that acidosis plays a significant role in osteoclasts formation and activation via up-regulating various genes responsible for its adhesion, migration, survival and bone matrix degradation. Understanding the role of acidosis in osteoclast biology may lead to development of novel therapeutic approaches for the treatment of diseases related to low bone mass. In this review, we aim to discuss the recent investigations into the effects of acidosis in osteoclast biology and the acid-sensing molecular mechanism.